Experimental Research on a Novel Frost-Free Air-Source Heat Pump Water Heater System - Wang Zhihua; Wang Fenghao; Zheng Yuxin; Li Jingchao; Huan Chao; Wang Zhiyang (Zhileng xuebao)
Aiming to the frosting problem of air-source heat pump (ASHP) at low temperatures, a novel frost-free air-source heat pump water heater (ASHPWH) system is proposed in the paper, in which dehumidification of solid desiccant is used to reduce the humidity ratios of ambient air to realize frost-free operation. In order to keep the system working continuously, phase-change thermal storage is used to recycle the condensation heat that acts as a low temperature resource to regenerate the solid desiccant. The novel system was compared experimentally with conventional defrost system at a temperature of 0 ℃ and relative humidity (RH) of 80%. The results show that the average COP of the system was increased by 7.25% and 46.3% in comparison with hot-gas bypass defrosting and electric resistance heating, which proves the feasibility of the novel system.